SERPINF1 gene variants causing late-onset progressive deforming osteogenesis imperfecta – A study of 18 patients from India - Agnes Selina; Madhavi Kandagaddala; Vignesh Kumar; Suneetha Susan Cleave Abraham; Sumita Danda; Vrisha Madhuri (Bone Reports, 2023)
SERPINF1 gene variants lead to a severe type of osteogenesis imperfecta (OI) attributed to defects in the matrix mineralization. We present 18 patients with SERPINF1 gene variants leading to severe progressive deforming OI, the largest series in the world to date. These patients were normal at birth and had the first fracture between 2 months to 9 years; progression of deformities was seen in 12 adolescents who became nonambulatory. Radiologically, compression fractures with kyphoscoliosis, protrusio acetabuli, and lytic lesions in the metaphysis and pelvis were seen in older children with classical popcorn appearance in the distal femoral metaphysis in three. By exome sequencing and targeted sequencing, we identified ten variants. One was unreported and novel; three other novel variants in this series were reported earlier. The recurrent deletion inframe mutation p.phe277del was found in 5 patients from three families. Alkaline phosphatase was elevated in all children on the first visit. Bone mineral density was low in all patients and showed improvement at two years in seven children on regular pamidronate therapy. For others, the 2 year BMD data were not available. The Z scores for four of the seven children showed worsening at the 2-year follow-up.